Measuring Indian Economic Progress : An Analysis of National Leadership Through Stock Market Performance - Venkata Raman, R.; Srinidhi, V. R.; Chandramouli, A. S. (Indian Journal of Finance, 2016)
India is among the most favoured nations in the world for investments because of sustainability, even as uncertainty prevails largely across the global financial markets. As India continues to maintain cordial investment policies towards FII investments, financial markets in India can attain greater heights in comparison to foreign financial markets. This qualitative-analytical and quasiquantitative study uses stock returns during the regime of four Indian Prime Ministers. The study concentrated on the performance of the stock market under present and past leaders of India with special reference to volatility in the stock market and business opportunities in India. Furthermore, the variables were measured by using descriptive statistics, Markov regime switching model, and economic conditions. This study revealed that political leadership and policy go hand in hand; balance between borrowings and investments is a must for a strong economy, and the study found that FDI is important for strengthening the Indian currency.